2016
DOI: 10.1002/2016gl070793
|View full text |Cite
|
Sign up to set email alerts
|

Mantle plumes beneath the South Pacific superswell revealed by finite frequency P tomography using regional seafloor and island data

Abstract: We present a new tomographic image beneath the South Pacific superswell, using finite frequency P wave travel time tomography with global and regional data. The regional stations include broadband ocean‐bottom seismograph stations. The tomographic image shows slow anomalies of 200‐300 km in diameter beneath most hot spots in the studied region, extending continuously from the shallow upper mantle to 400 km depth. Narrow and weak slow anomalies are detected at depths of 500–1000 km, connecting the upper mantle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…We used the P-velocity model obtained by Obayashi et al (2016) using data from the Tomographic Investigation by seafloor Array Experiment for the Society hot spot (TIARES) BBOBS network (Suetsugu et al 2012) as the part of global data set including the arrival time data from the International Seismological Centre. The travel times of the TIARES BBOBS network were estimated for all the same events used for the tomography, and root mean The synthetic experiment indicated that shallowlayer reverberation could influence the cross-correlation measurements of the relative travel time among a BBOBS array at periods longer than 10 s. We proposed a simple method to correct differential P-wave travel times between two sites for shallow-layer reverberation by cross-convolution of the shallow-layer responses at the two sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the P-velocity model obtained by Obayashi et al (2016) using data from the Tomographic Investigation by seafloor Array Experiment for the Society hot spot (TIARES) BBOBS network (Suetsugu et al 2012) as the part of global data set including the arrival time data from the International Seismological Centre. The travel times of the TIARES BBOBS network were estimated for all the same events used for the tomography, and root mean The synthetic experiment indicated that shallowlayer reverberation could influence the cross-correlation measurements of the relative travel time among a BBOBS array at periods longer than 10 s. We proposed a simple method to correct differential P-wave travel times between two sites for shallow-layer reverberation by cross-convolution of the shallow-layer responses at the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we estimated the effects on P-wave travel times measured with waveform cross-correlation and their frequency dependence by calculating synthetic seismograms using realistic shallow-layer models. In addition, we estimated the shallow-layer effect on the measurement of relative travel times of teleseismic P-waves recorded by an oceanic seismic array, which is a common method to extract the travel time information of teleseismic P-waves from BBOBS data (e.g., Wolfe et al 2009Wolfe et al , 2011Obayashi et al 2013Obayashi et al , 2016. We were then able to propose a simple method to correct the relative travel times for shallow-layer reverberation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this 630-day observation, more than 800 We plan to apply seismic tomography to the data from the OJP array and permanent seismic stations located in the Pacific Ocean to determine three-dimensional seismic velocity structures of the upper mantle beneath the OJP using body wave traveltime tomography (e.g., Obayashi et al, 2016) and surface wave tomography (e.g., Isse et al, 2016) with unprecedented spatial resolution. The lateral and vertical extents of the previously found low-velocity Theoretical traveltime curves predicted by the iasp91 model (Kennett and Engdahl, 1991) are also shown by red lines.…”
Section: Suetsugu Et Almentioning
confidence: 99%